21st Century Trend of Water Yield in River Basins of Guinea and Sudano-Sahelian Ecological Zones, Nigeria - A. C, Salihu; A, Abdulkadir; G. N, Nsofor; M. Y, Otache; S, Ojoye (International Journal of Climate Research, 2020)
In Nigeria, the climate in recent years has witnessed significant variability across the various ecological zones due to climate change. Thus, the objective of this study was to analyse the 21st century trend of water yield in river basins of Guinea and Sudano-Sahelian ecological zones, Nigeria. The data and computation were done using KNMI Climate Explorer. The coordinates of the basins were used to derive the annual and seasonal water yield. Projections were produced for near-term (2019-2048), mid-term (2049-2078) and long-term (2079-2100) using ensemble mean of CMIP5 under RCP2.6, RCP4.5 and RCP8.5. Findings revealed that water yield during dry season demonstrates decreasing range of (-0.05 to -0.1 mm/day). It was observed that the decrease were only significant for RCP8.5 but not under middle and low emission trajectories. As for wet season, it reveals significant increasing trends at 0.05 significant levels with respect to RCP8.5 but not significant in low and middle emission scenarios. Regional trend analysis of average annual water yields reveals no significant positive trends for all the RCPs. This is to say that despite the projected increasing pattern of average annual water yield observed over Guinea and Sudano-Sahelian ecological zones, incidences of water crisis cannot be ruled out.